Modern and fossil siliciclastic sediments colonized by microbial mats. A comparative study for analog determination. (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The present study is based on the comparison between siliciclastic sedimentary deposits of both, paleo- and modern environments in which microbial activity has been recognized in sediments, leading to the establishment of analogues. This fact leads up to the characterization of microbial sedimentary structures and the comprehension of the physical- chemical and biological processes of their formation and modification. Different characteristics are com- pared in both environments: sedimentary fabrics, grain size, mineralogical composition presence of microorganisms or microbial activity remnants, and sedimentary structures. The objective is to under- stand the occurrence of such characteristics, the mechanisms of formation that acted in the past and their relationship with the environmental conditions. In addition, the presence of microbial mats in the fossil environment is discussed as an agent for the preservation of the ichnites and archaeological remains after an early lithification.The archaeological localities of “La Olla” and “Monte Hermoso I” are studied (Fig. 1). They are characterized by an excellent conservation of organic remains associated with human activity, and the preservation of human footprints, respectively. Both deposits are Holocene sediments, currently located in the lower- and middle- intertidal area of a modern beach. The remarkable preservation of traces of extinct mammals (the most remarkable is the huge ground sloth Megatherium), birds, and vertebrates at the Pehuen Có paleoichnological site, has also been documented. These sediments correspond to late Pleistocene, and are currently located in the upper- intertidal zone where is sometimes covered by sand after storm events. All these fossil sedimentary deposits are located on the coast of SE Buenos Aires. Modern environments, Bahía Blanca Estuary and the paleo-channel of Paso Seco, were studied (Fig. 1). Several microbial induced sedimentary structures have been found and were related to the hydrodynamic processes.Direct observation of microbial sedimentary structures present in the supra-tidal zone of Bahia Blanca Estuary and coastal area in Paso Seco were compared with sedimentary structures expose in the fossil deposits. Also, various analyses to determine the sedimentary arrangement and textural features have been applied. Micrographs obtained from the scanning electron microscope (SEM) have allowed the identification of the interaction of the sediments with microorganisms, recognizing the substances generated by them (EPS, extracellular polymeric substances) and the presence of authigenic mine- rals, such as pyrite as geochemical product of the bacterial metabolism. Analysis of thin sections show the sedimentary fabric associated with the presence of cyanobacteria. X-ray analysis allowed determining authigenic minerals such as biogenic calcite, magnesian calcite, and dolomite.The relevant characteristics of the deposits asso- ciated with the presence of microbial activity are documented in detail. The identification of millimeter to centimeter thickness lamination, fine and coarse sedimentation stands out (Fig. 2) which is the most remarkable characteristic of the presence of microbial activity recognized as biolamination (Fig. 4). Thisalternation can be clearly documented in modern environment with specific details as light crinkled lamination and the presence of EPS that amalgamate the siliciclastic grains. Thin and coarse alternation contributes to another common characteristic that is the bimodal distribution in granulometric sediment analyses (Fig. 4). Petrographic thin sections were observed under a petrographic microscope (Fig. 5). Both environments, ancient and modern sediments, present similar characteristics. The biolamination with diffuse border in the fossil sample, sometimes waving, in light and dark brown laminae can be appreciated. The biolaminites can be discriminated in modern samples. The alternation with coarse sediment (sands) reflects the hydrodynamic condi- tions of the area, a change towards a greater energy level. Micrographs obtained from SEM under fossil samples reveal the presence of bacteria, EPS, diatoms, and authigenic minerals as pyrite (Figs. 6, 7). The micrographs from the modern environment show the sedimentological-biological relationship in the microbial mat and authigenic precipitates.Several microbial sedimentary structures were recognized in La Olla site (Fig. 8). They are: a) biolamination; b) presence of bubbles generated by microorganism metabolisms and entrapped by biofilm; c) elephant skin texture; d) plant and arqueological rests entrapped by the microbial mat colonization; e) microbial folds; f) mat deformation. Also, in El Pisadero site in the archaeological locality Monte Hermoso I, an special configuration were observed that was defined as deformed structure by load pressure and injection of underlying mat, related to the weight of individuals that had walked on the microbial mat surface (Fig. 8h, i). In the Pehuen Có paleo-ichnological site, the most conspicuous structures are the huge ground sloths footprints with a marginal erosioned rim exposing the lamination (Fig. 9). There is also a high ichnodiversity preservation of mammal and bird tracks showing the high vertebrate biodiversity du- ring the late Pleistocene in southern South America. To confirm the presence of microbial mats, several others microbial sedimentary structures and textures were recognized, biolaminites, wrinkle marks, bubbles, colonized plant rests, mat chips, desiccation cracks, and preserved ripples. The laminated siltstone erosion is common. In the colonized modern supra-tidal plain in Bahía Blanca Estuary, several microbial sedimentary structuresrelated to physical processes as storm events were documented: flipped-over mats, erosional pockets, microbial mat chips, and desiccation cracks with recolonization due to successive inundation. In Paso Seco, the characteristic cohesive and flexible behavior of mats was recognized by the presence of microbial domes with diameter > 12 cm (Fig. 10), and deformed microbial structures as folds, and roll- ups. These structures are formed as a consequence of water friction associated to high tide-related currents flooding in an ancient channel. The mat growing in the supratidal area during calm conditions may involve several days or months when the tide reaches the zone during spring-tides. It can also grow over shells or plants in the modern or fossil sites (Figs. 8c, 11).The mat activity can be inferred by the formation of bubbles or domes with different sizes depending on the microbial thickness and different stages of evolution (Fig. 12). Similar bubbles were found in the fossil environment and analogous process can be suggested to their formation (Fig. 13). Also, the ancient or modern desiccation cracks represent constant periods of exposition in a supratidal zone. Conversely, other sedimentary structures are formed as a response to physical process as water currents or waves acting on microbial mats (Fig. 14). In that case, erosional pockets and remnants, microbial chips, and folds were compared in the fossil and mo- dern environments. The characteristically plasticity and cohesiveness of the microbial mat under wet conditions favors mat deformation.Finally, the relevance of microbial mats in modi- fying the erosional threshold, and the conditions needed for the formation of footprints over a microbial mat are discussed. Also, the role of microbial mats in the preservation of ichnites by means of stability and early lithification is recognized.
Keywords: Lamination, Bioestabilization, Ichnites preservation, Fossil and modern records, Atlantic coast, Argentina.